The potential of sago larva as insect meal for poultry feed: preliminary study - Danung Nur Adli (Universitas Tidar, 2020)
Indonesia were an island countries which is had a huge biodiversity. The one of potential were to produce the insect meal as an alternatives source of protein in Indonesia. The research purposes to determine of possibility of sago larvae meal as insect meal for poultry feed. A review and materials were sago warm meal from Moluccas and Papua determined using proximate analysis. The data were analyzed using SAS Version Red hat University 64-bit. The result showed the sago larva were significant differences on (p < 0.05) on protein and metabolizable energy. It can be concluded sago larva meal has positive result on as poultry feed in the future.